MARS/NDRI/KSU Communications Workshop: Part 7C. Nominal Groups & Discussion Strategies - Leslie, John F. (My University, 2022)
Moderated discussion process • In use since the 1970s • Used for mycotoxin discussions in Africa, China, Afghanistan, the US and Europe • Goals: • Equal input from all participants • Large number of ideas with rankings • Generating new thoughts and thought combinations
Keywords: Aflatoxin; Food Safety; Mycotoxins; Nepal; Public Health; Risk Communication